Eesti elanike meediatarbimine ja võimalikud seosed usuliste ning moraalsete tõekspidamistega uuringu „Elust, usust ja usuelust 2020“ põhjal - Kangro, Hele-Maria; Lilleoja, Laur (Usuteaduslik Ajakiri, 2024)
Media Consumption Among Estonian Residents and Its Connection to Religious and Moral Beliefs: Insights from the ’On Life, Faith, and Religious Life 2020’ Study The focus of this article is analyzing whether there could be any associations between media consumption and personal moral and religious beliefs among Estonian residents. The analyses are based on data from survey „Elust, usust ja usuelust 2020“. Empirical part of this paper included two steps. In the first step most common media consumption patterns are identified, resulting in 5 distinct classes. Second step focuses on relationships. Reveled associations were most pronounced among consumers of Christian media, who had a distinctly more conservative stance on the moral permissibility of divorce, abortion, euthanasia, human cloning, etc. Another group which was relatively more open for religiosity, included respondents who avoided news.